Investigation of Serum Cartonectin Concentrations in Pregnant Women with Gestational Diabetes Mellitus; a Prospective Non-Interventional Cohort Study - Onur Gebes; İbrahim Kale; Tuba Beser Gebes; Murat Muhcu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate serum cartonectin concentrations in pregnant women diagnosed with Gestational Diabetes Mellitus (GDM).